Relatos de resistencia: Crónicas venezolanas, crisis política y estado de excepción en Venezuela (1992-2021) - Cavallin Calanche, Claudia (My University, 2022)
During a deep crisis in a historical, political, and social context, the chronicles are published as mechanisms before a state of emergency in Venezuela can be included in the annals, as a close, direct, and plausible reference to the difficult dictatorial political system that the Venezuelans faced for many years. Read from another context, the writing of current Venezuelan chronicles transcends geographical margins and strengthens thought from exile. Therefore, Latin American writers, and especially Venezuelans, continue to assume the commitment to wield the stories that detail what happens in contemporary Venezuela. In this investigation, each chronicle is assumed to be historical and political writing in a state of exception.
Keywords: literature; journalism; history